A comparative analysis of photometric parameters of the Jupiter Galilean satellites' surfaces - V. I. Shavlovskij (Вісник Астрономічної школи, 2016)
The Hapke's model parameters (w, g, h and B_0) were obtained separately for leading and trailing hemispheres of the Galilean satellites of Jupiter by using the ground-based narrow band photoelectric observations. The values of the obtained parameters confirm existence of hemispherical dichotomies in the photometric characteristics of Galilean satellites surfaces. The obtained values of the half-width at the half-maximum (HWHM) of the opposition peak prove that the opposition effects of Io and Europa are caused by coherent backscattering.